Evaluation method for resource potential of shale oil in the Triassic Yanchang Formation of the Ordos Basin, China. Issue 4 (July 2020) - Guo, Qiulin; Chen, Xiaoming; Liuzhuang, Xiaoxue; Yang, Zhi; Zheng, Man; Chen, Ningsheng; Mi, Jingkui
The widely distributed, thick Chang 7 Shale is the richest shale oil formation in China. A calculation method for the evaporative hydrocarbon recovery coefficient based on formation volume factor is proposed considering the correction of heterogeneity-based total organic carbon differences to improve the adsorbed oil calculation method, and light hydrocarbon evaporative sampling losses, which can make mobile and total oil calculations more accurate. The adsorbed oil, S1 evaporative loss, total oil yield, and movable oil yield of 200 shale samples from the Chang 7 Member were calculated using the new methods. Results show that S1 evaporative loss accounts for 29% of S1, total oil yield is 3.5 times S1, and movable oil yield accounts for 37% of total oil yield. Based on the calculated total oil yield and movable oil yield results, the relationships among total oil yield, movable oil yield, and total organic carbon of the Chang 7 were established yielding total oil yield and movable oil yield estimates of 11.12 × 10 9 t and 4.01 × 10 9 t, respectively, revealing its tremendous shale exploration potential.